Vozrastnye osobennosti osvoeniya tekhniki krugovogo pedalirovaniya - Popkov, V. N. (Teorija i Praktika fiziceskoj Kul'tury, 2000)
The purpose of the study was to reveal the age regularities of motor function in children and teenagers at the process of many years training.